Advances in Optical and Mechanical Technologies for Telescopes and Instrumentation 2014
DOI: 10.1117/12.2054700
|View full text |Cite
|
Sign up to set email alerts
|

Developing engineering model Cobra fiber positioners for the Subaru Telescope’s prime focus spectrometer

Abstract: The Cobra fiber positioner is being developed by the California Institute of Technology (CIT) and the Jet Propulsion Laboratory (JPL) for the Prime Focus Spectrograph (PFS) instrument that will be installed at the Subaru Telescope on Mauna Kea, Hawaii. PFS is a fiber fed multi-object spectrometer that uses an array of Cobra fiber positioners to rapidly reconfigure 2394 optical fibers at the prime focus of the Subaru Telescope that are capable of positioning a fiber to within 5µm of a specified target location.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…5): After several years of prototyping and testing activities, 17 we recently started the mass production of the Cobras at New Scale Technologies. About 500 units have already been delivered as of Jun 2016.…”
Section: The Instrument Developmentmentioning
confidence: 99%
“…5): After several years of prototyping and testing activities, 17 we recently started the mass production of the Cobras at New Scale Technologies. About 500 units have already been delivered as of Jun 2016.…”
Section: The Instrument Developmentmentioning
confidence: 99%
“…Therefore, no particular measure has to be considered to avoid the collisions. Others that have rigid parts 5,10 have to avoid the collision between adjacent positioners. Some solutions have reported that handling the movement speed would suffice for avoiding the collision.…”
Section: Architecture Requirementsmentioning
confidence: 99%
“…PFS will accomplish the spectroscopic aspect of this project, and HSC has been implementing the imaging part since first light in 2012. : fiber system, 4-9 fiber positioner 10 and prime focus instrument, 11 spectrograph, [12][13][14] Dewar and detector, [15][16][17][18] and metrology camera. 3 PFS has now entered the construction phase, and Fig.…”
Section: Introductionmentioning
confidence: 99%